The general concept of evaluation of the electromagnetic environment in the zones of radio equipment operation of air traffic service companies - Конахович, Г. Ф.; Іванов, В. О.; Ільницький, Л. Я.; Курушкін, В. Є. (Proceedings of National Aviation University, 2002)
A new concept for assessing the quality of the electromagnetic environment at the point of location of the radio antenna is considered, and the connection of the level of noise at the receiver input with the level of the useful signal with a known protective relation is considered.